Urban Samnium? Towards a Literary and Archaeological Re-evaluation - Lee, Kevin S. (Journal of Urban Archaeology, 2022)
Abstract The Samnites ringed southern Italian mountains with monumental fortified centres. Livy and Strabo referred to some as urbes/oppida and πόλεις. Modern scholars, however, interpret these hillforts, which lack the monumental architecture and street grid expected of ancient Mediterranean cities, as non- or proto-urban. I contend Samnite hillforts, in concert with ancient sources, expand our ideas about Mediterranean urbanism. Livy and Strabo prioritized urban functions over appearance. I apply this understanding to the evidence from seven excavated centres as a first step towards archaeologically investigating Samnite hillforts as cities.